Pengaruh Kinerja Lingkungan, Kepemilikan Manajerial TerHadap Pengungkapan Corporate Social responsibility - Kholifah, Siti (MAKSIMUM: Media Akuntansi Universitas Muhammadiyah Semarang, 2022)
This study aims to analyze the effect of the audit committee, environmental performance, profitability, and managerial ownership on the disclosure of corporate social responsibility in manufacturing companies in Indonesia. The research approach used is descriptive verification analysis using secondary data. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange in 2015–2019. The sampling technique used is non-probability sampling using purposive sampling method. Statistical analysis used in this study is multiple linear regression. The results of this study indicate that the audit committee, environmental performance, and profitability have a positive effect on the disclosure of corporate social responsibility. Meanwhile, managerial ownership has a negative effect on the disclosure of corporate social responsibility.